2017
DOI: 10.1039/c6ra26601k
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal properties of millimeter-scale alumina aerogel beads formed by a modified ball dropping method

Abstract: We report the formation of alumina aerogel beads with a modified ball dropping method, in which alumina alcogel beads are formed by extruding alumina sol containing a small amount of polyvinyl alcohol through nozzles into ammonia water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…37 In this work we have prepared X-alginate aerogels in the form of beads, which have several advantages compared to monoliths, for example fewer defects, 46 easier processing via accelerated solvent exchange and continuous supercritical drying, 47 and closer proximity to applications. [48][49][50][51][52][53][54] Indeed, although isolated cases of aerogel beads based on inorganic materials, 51,[54][55][56] and organic polymers 10 have also been reported, almost all biopolymer aerogels in the literature are prepared in the form of beads, because, in addition to the above advantages, fast gelation renders the procedure of making biopolymer aerogel beads more straightforward than making monoliths, and easily scalable. 48,49,57,58 Finally, this new class of materials has been expanded to include crosslinked chitosan (X-chitosan) aerogel beads, thus suggesting the generality of this method for other biopolymer aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…37 In this work we have prepared X-alginate aerogels in the form of beads, which have several advantages compared to monoliths, for example fewer defects, 46 easier processing via accelerated solvent exchange and continuous supercritical drying, 47 and closer proximity to applications. [48][49][50][51][52][53][54] Indeed, although isolated cases of aerogel beads based on inorganic materials, 51,[54][55][56] and organic polymers 10 have also been reported, almost all biopolymer aerogels in the literature are prepared in the form of beads, because, in addition to the above advantages, fast gelation renders the procedure of making biopolymer aerogel beads more straightforward than making monoliths, and easily scalable. 48,49,57,58 Finally, this new class of materials has been expanded to include crosslinked chitosan (X-chitosan) aerogel beads, thus suggesting the generality of this method for other biopolymer aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…The band around 3400 cm −1 is also assigned to physisorbed water and the shoulders of this band at 3300 and 3090 cm −1 correspond to (Al)O−H stretching modes of boehmite . The bands at 476, 617, 777 and the shoulder at 1065 cm −1 are ascribed to the Al–O–H vibrations of boehmite …”
Section: Resultsmentioning
confidence: 99%
“…In the magnified image of the dense region ( Figure 3(a4,b4)), it was identified that compactly stacked regular arrays of nanotubes were formed in the preparation process. This compact array structure would be beneficial for heat transfer applications as bed material in the fluidized bed [21], because a highly dense nanotubes layer can increase thermal conductivity as well as electrical conductivity between the nanotubes [22]. In analyzing shape information, circularity and solidity are defined as follows [8,19].…”
Section: Physical and Thermal Propertiesmentioning
confidence: 99%
“…It is believed that the surfactant weakens the coagulation of the nanotubes on the surface of initially formed microbead, thereby providing an opportunity to smoothly recoagulate the surface shape of the bead in the mechanical rolling step (Figure 3(b2)). On the other hand, case I dropped in pure water is difficult to form sphere due to low spherical drop formation from nozzle by high viscosity of the paste [21], and strong coagulation in the water, as seen from the overlapped surface layers in Figure 3(a2).…”
Section: Physical and Thermal Propertiesmentioning
confidence: 99%